2022
DOI: 10.3389/ffutr.2022.913887
|View full text |Cite
|
Sign up to set email alerts
|

Tram to Pedestrian Collisions—Priorities and Potentials

Abstract: To improve mobility in cities in line with environmental goals, in urban traffic, trams represent an increasingly important means of transport. Due to the close interaction with other road users, this makes collisions with trams fairly frequent. This study has investigated accidents between trams and vulnerable road users resulting in personal injury, aimed at identifying priorities for simulating collisions between trams and pedestrians to assess passive safety measures. Tram accident data collection establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…According to the reports from Swedish emergency hospital departments, femur and tibia fractures were the main form of lower limb injury for pedestrians in tram crashes [5], which is consistent with the findings of this paper. Additionally, Christine et al's study [17] identified instances where tibial accelerations surpassed safety thresholds, consistently exceeding femoral accelerations overall.…”
Section: Bone Fracture Severitysupporting
confidence: 91%
See 4 more Smart Citations
“…According to the reports from Swedish emergency hospital departments, femur and tibia fractures were the main form of lower limb injury for pedestrians in tram crashes [5], which is consistent with the findings of this paper. Additionally, Christine et al's study [17] identified instances where tibial accelerations surpassed safety thresholds, consistently exceeding femoral accelerations overall.…”
Section: Bone Fracture Severitysupporting
confidence: 91%
“…In particular, in the collision scenario with α = −90 • , there was not only the highest risk of brain contusion but also a high risk of facial bone fracture (including nasal and maxillary fractures) due to the direct action of the impact force on the face. This is also reflected in accident statistics, which show that 57 out of 554 tram-pedestrian collisions in Sweden between 2000 and 2021 involved facial fractures [5].…”
Section: Brain Contusion Severitymentioning
confidence: 92%
See 3 more Smart Citations